Disconnect : the Filipino comfort women - Rosello, Cristina Lope Yl. (Cristina Lope Ylanan) (Diliman, Quezon City, Philippines : Gates Pub., 2011)
"Disconnect: The Filipino Comfort Women" uses an existential-phenomenological perspective as it tackles the war experiences of elderly survivors of rape. The psychologist addresses the women's psychological trauma which has lasted more than fifty years after WWII. To heal their inner wounds, the women explore the meaning of their suffering, no matter how underserved it may be. In so doing, they eventually understand existential issues of mortality and dread. Creative, artistic expressions, in particular, drawings of hypnotic images of a garden served as the medium for phenomenological dialogues that ultimately led to full disclosure and unraveling of inner fragmentation."
From victims to survivors -- Trauma stories -- Making meaning of war -- The Pacific War -- "I and thou"
Includes bibliographical references (p. 179-186).
Keywords: Comfort women -- Philippines; Comfort women -- Counseling of -- Philippines; World War, 1939-1945 -- Personal narratives, Philippine